Perkawinan Negen Dadua sebagai Wujud Kesetaraan Gender dalam Masyarakat Hukum Adat Bali - Wedanti, I Gusti Ayu Jatiana Manik; Windia, I Wayan P; Sudantra, I Ketut (SINTHOP: Media Kajian Pendidikan, Agama, Sosial dan Budaya, 2023)
This article examines the concept of Negen Dadua marriage in Bali, a unique form of marriage recognized within Balinese Customary Law. This concept has emerged as a solution to inheritance and lineage issues, particularly in families without male children. The research method employed is normative-conceptual, utilizing primary and secondary legal sources. The analysis reveals that Negen Dadua marriage, recognized under national and Balinese customary law, accords both husband and wife the status of purusa, allowing them to maintain responsibilities and rights within their respective families. This study finds that Negen Dadua marriage not only complies with Balinese Customary Law and Hindu religion but also reflects a shift towards gender equality. It offers a solution to the inequity in inheritance and social roles between men and women. This indicates a positive development in social and legal awareness of gender equality in Bali, especially in family law. This marriage form, embodying gender equality, presents an efficient solution to inheritance issues without disadvantaging any party. The article concludes that Negen Dadua marriage is a manifestation of gender equality within the Balinese Customary Law community and represents a progressive step towards recognizing women's rights. Abstrak Artikel ini mengkaji Perkawinan Negen Dadua di Bali, yang merupakan bentuk perkawinan alternatif dalam Hukum Adat Bali. Konsep ini muncul sebagai solusi untuk masalah pewarisan dan keturunan, terutama di keluarga tanpa anak laki-laki. Metode penelitian adalah normatif konseptual, menggunakan sumber hukum primer dan sekunder. Analisis menunjukkan bahwa perkawinan negen dadua, diakui dalam hukum nasional dan adat Bali, memberikan status purusa kepada kedua suami dan istri, memungkinkan mereka mempertahankan tanggung jawab dan hak dalam keluarga masing-masing. Studi ini menemukan bahwa perkawinan negen dadua bukan hanya mematuhi Hukum Adat Bali dan agama Hindu, tetapi juga mencerminkan pergeseran menuju kesetaraan gender, menawarkan solusi untuk ketidaksetaraan dalam pewarisan dan peran sosial antara laki-laki dan perempuan. Ini mengindikasikan perkembangan positif dalam kesadaran sosial dan hukum tentang kesetaraan gender di Bali, khususnya dalam hukum keluarga. Perkawinan ini, sebagai wujud kesetaraan gender, menawarkan solusi efisien untuk masalah pewarisan tanpa merugikan pihak mana pun. Artikel ini menyimpulkan bahwa perkawinan negen dadua adalah manifestasi dari kesetaraan gender dalam masyarakat Hukum Adat Bali dan merupakan langkah maju menuju pengakuan hak-hak perempuan.